Mobile Tower Radiation and Its Impacts on Child Health: a Study Conducted in an Ecologically Sensitive Area of Western Ghats - Premlal P. D; Eldose N. V (Institute of Advanced Engineering and Science, 2018)
The effect of mobile tower radiation on child health in an ecologically sensitive area of Western Ghats in Idukki, Kerala is studied. In this paper, we have attempted to discover whether any relation exists between the RF exposure and the health of children under 15 years old. At some point of path of this work, twenty common diseases were considered. From our analysis, it has been discovered that five of them are very much related to RF exposure. Furthermore, the age group between ten to fifteen years is more vulnerable to mobile tower radiation, and boys are observed to be more affected than girls. In the region under study, exposure levels were well below the ICNIRP recommendations and the current Indian standards. However, still it is inadequate to safeguard children. So it is recommended to modify the current Indian standard of RF exposure.